2012
DOI: 10.1088/1751-8113/45/37/374012
|View full text |Cite
|
Sign up to set email alerts
|

Quantum vacuum interaction between two sine-Gordon kinks

Abstract: We calculate the quantum vacuum interaction energy between two kinks of the sine-Gordon equation. Using the T GT G-formula, the problem is reduced to the known formulas for quantum fluctuations in the background of a single kink. This interaction induces an attractive force between the kinks in parallel to the Casimir force between conducting mirrors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 19 publications
(36 reference statements)
2
38
0
Order By: Relevance
“…Therefore the condition ψ(0) = ψ(L) does not necessarily give rise to periodic boundary conditions. As an example it is worth to mention the case of Dirac delta potentials (see references [26][27][28] for recent developments in the interpretation of Dirac delta potentials as boundary conditions and infinitely thin kinks) where the condition ψ(0) = ψ(L) is satisfied but obviously the system does not satisfy periodic boundary conditions. Therefore in order to distinguish periodic boundary conditions from other types of point interactions it is necessary to include the second condition over the derivatives: ψ (0) = ψ (L).…”
Section: Heat Kernel Coefficients For Common Boundary Conditionsmentioning
confidence: 99%
“…Therefore the condition ψ(0) = ψ(L) does not necessarily give rise to periodic boundary conditions. As an example it is worth to mention the case of Dirac delta potentials (see references [26][27][28] for recent developments in the interpretation of Dirac delta potentials as boundary conditions and infinitely thin kinks) where the condition ψ(0) = ψ(L) is satisfied but obviously the system does not satisfy periodic boundary conditions. Therefore in order to distinguish periodic boundary conditions from other types of point interactions it is necessary to include the second condition over the derivatives: ψ (0) = ψ (L).…”
Section: Heat Kernel Coefficients For Common Boundary Conditionsmentioning
confidence: 99%
“…Particularly, they have calculated the vacuum energy and identified which boundary conditions generate attractive or repulsive Casimir forces between the plates. Bordag and Muñoz-Castañeda [66] have calculated the quantum vacuum interaction energy between two kinks of the sine-Gordon equation (for a review on nonlinear localized excitations including topological solitons see, e.g., the work [67]) and shown that this interaction induces an attractive force between the kinks in parallel to the Casimir force between conducting mirrors. A rigorous mathematical model of real metamaterials has been suggested in [68].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, configurations of two pure delta potentials added to the free Schrödinger Hamiltonian have been used to describe scalar field fluctuations on external backgrounds [25], in terms of the corresponding scattering waves. Delta point interactions allow the implementation of some boundary conditions compatible with a scalar QFT defined on an interval [26]. The delta interaction is often multiplied by a real number a.…”
Section: Introductionmentioning
confidence: 99%